PENGARUH DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KOMITMEN ORGANISASI DAN KINERJA PEGAWAI INSPEKTORAT KABUPATEN KAMPAR - Wulan Wulan; Pirmansyah Pirmansyah; Dessy Kumala Dewi (JURNAL ECONOMICA: Media Komunikasi ISEI Riau, 2024)
This study aims to determine and examine the effect of work discipline, work motivation on organization commitment and the performance of the Kampar Regency Inspectorate employees. This research was conducted at the Kampar Regency Inspectorate Office with a population of 82 people. The research sampling technique used the census method where all the population was sampled with a total of 82 respondents. Data analysis techniques used descriptive and quantitative. Hypothesis testing using descriptive analysis and Structure Equation Model (SEM) with the help of Smart PLS software. The results of hypothesis testing indicate that work discipline has no significant effect on organization commitment and employee performance, work motivation has no significant effect on organization commitment and employee performance. organization commitment has a positive and significant effect on employee performance. From the test results the coefficient of determination (R2) shows a very weak effect. Because the exogenous variable in explaining the endogenous variable for the structure of model 1 is 0.5%. So that the variables outside the model that are not studied have a greater influence. The structure of model 2 is also the same as the structure of model 1 where exogenous variables can explain endogenous variables by 5.4%, meaning that variables outside the model have a greater influence than the model studied.